FUNGSI KOMITE SEKOLAH DALAM PENGEMBANGAN DAN IMPLEMENTASI PROGRAM SEKOLAH DI SD NEGERI 19 BANDA ACEH - Sulaiman Sulaiman; Nurmasyitah Nurmasyitah; Mislinawati Mislinawati (Jurnal Pesona Dasar, 2019)
This research raises the problem of how the school Committee functions in the Development and implementation of school programs at SD Negeri 19 Banda Aceh. This research aims to describe the function of the school committee in the Development and implementation of school programs in SD Negeri 19 Banda Aceh. The subject of this study is a school committee administrator who is directly involved in management. The number of research subjects is as many as 22 people. The method used is an analytical description method with a qualitative approach. Data collection is done by non-test techniques in the form of poll and data processing in the form of percentage calculations. The research results that the school Committee plays a role in determining school policies. The role of the school Committee is limited to receiving reports from the school principal. The school committee was poorly involved in taking the school's policies. The school committee is only involved when raising funds from the community. The conclusion of the research is the function of the school committee in the Development and implementation of the school program at SD Negeri 19 Banda Aceh is still small. The involvement of school committees in the development and implementation of school programs in SD Negeri 19 Banda Aceh is only 36.37%. The school committee will be fully functional involved by the school if it has to do with the school's luminescence that requires community assistance.